Who are Europe's efficient bankers? - Rien Wagenvoort; Paul Schure (EIB Papers, 1999)
On the first of January 1993, the Second Banking Directive (1989) of the European Union and a number of the other EU Directives (1) related to the financial service industry were implemented. This heralded a new episode of deregulation, standardised minimum capital requirements and changes in supervision rules and deposit-guarantee schemes. The single passport and mutual recognition have cleared the road for cross-border banking, while the introduction of the single currency on the first of January 1999 took away one of the last obstacles for a competitive and integrated banking market. The general belief among bankers and academics is that competition has significantly increased in this changing European banking environment. Indeed, the numerous cases of recent mergers and acquisitions in the financial world would indicate that bankers and insurers are trying to reshape their businesses into more profitable and lean (cost efficient) institutions in order to face national and global competitive pressures. Traditional income streams such as interest margins have dried up, whereas new sources of revenues such as brokerage services, investment banking products, risk management and portfolio management have become more and more important. Besides major changes in the regulatory environment, the banking industry will be further modernised by the implementation of new computer technologies.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Bankenpolitik; Bank; Wettbewerb; Wirtschaftliche Effizienz; EU-Staaten